Pengaruh Lama Penyinaran dan Salinitas terhadap Pertumbuhan dan Jumlah Klorofil A Sargassum sp. [Effect Of Photoperiod And Salinity On The Growth And Chlorophyll A From Sargassum sp. ] - Moch. Amin Alamsjah; Maya Kartika Eismaputeri; Boedi Setya Rahardja (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Growth of Sargassum sp. in the waters of the world is different in each of its waters, it is strongly influenced by several factors, namely salinity and photoperiod. Salinity is closely related to the osmotic pressure that effects the body's balance of aquatic organisms. Photoperiod effects directly or indirectly, in particular on the algae, namely as a source of energy for photosynthesis. Photosynthesis process will occur not only with light, but also with the help of chlorophyll. The aim of this study was to determine the effect of photoperiod and salinity on growth and chlorophyll a Sargassum sp. and to determine the interaction relationship between photoperiod and of salinity on growth and chlorophyll a Sargassum sp. The design of the study is a Completely Randomized Design (CRD) Factorial test followed by Duncan's Multiple distance. Materials used in this study is Sargassum sp. with 9 treatments and 3 replications. Data results showed that the effect of salinity was not significantly different (F calculated < F table 0.05) on the growth of Sargassum sp. Effect of photoperiod did not different significant on the growth of Sargassum sp. in the first week until the third week, but different very significant (F calculated> F table 0.01) in the fourth week of treatment where E is the salinity of 30 ppt with photoperiod light 16 and 8 hours dark that significantly different with A, C, D, F, and I which not significantly different with B, G, H. On growth, there is no interaction of salinity and photoperiod. On chlorophyll a there is no difference significant in treatment A, B, C, D, E, F, G, H, and I. Salinity and photoperiod had no effect on chlorophyll a Sargassum sp., and there is no interaction of salinity and photoperiod.